The Mechanical Properties of Concrete Containing Glass Waste as Fine Aggregates and Rice Husk Ash as Cementitious Material - Mangi, Sajjad Ali; Shaikh, Shahid Ali; Ramu, Madhusudhan Bangalore; Said, Ahsan; Soomro, Saeed Ahmed; Kumar, Ram (Engineering, Technology & Applied Science Research, 2025)
The increase in the urban population has created a greater demand for infrastructure development. As a result, the use of construction materials, such as cement and fine aggregates, has significantly increased. Cement, a key component of concrete, is not only costly due to its high energy consumption, but also contributes substantially to environmental pollution through the emission of CO2 during production. Similarly, fine aggregates are widely utilized as fillers in concrete and are also expensive. In response to these challenges, researchers are investigating sustainable, eco-friendly, and cost-effective alternatives to reduce the environmental impact of construction. This research aims to assess the performance of concrete by partially substituting Ordinary Portland Cement (OPC) with Rice Husk Ash (RHA) and replacing fine aggregates with Glass Waste (WG) in varying proportions of 10%, 20%, and 30%. Ten concrete mixtures were prepared using M15 grade concrete with a 1:2:4 mix ratio and a water-cement ratio of 0.55. These included a control mix, individual mixes with RHA and GW, and combined mixes with equal proportions of both materials. The concrete samples were tested for workability, compressive strength, and split tensile strength. The results showed that RHA decreased the workability, while GW improved it. The compressive strength was optimal at 20% RHA and at a combined 10% RHA and 10% GW. GW alone also performed well at 20% replacement. The tensile strength was the highest with 10% RHA, 10% GW, and their 10% combination after 7 days and 28 days of curing. These findings confirm the potential of RHA and GW to serve as sustainable alternatives in concrete, helping to manage the solid waste, reduce the landfill use, lower the material costs, conserve the natural resources, and support environmentally friendly construction practices.